SISTEM SOSIAL ALA NIKLASH LUHMAN DALAM NOVEL SEPERTIGA MALAM DI MANHATTAN KARYA ARUMI E - Anton Wahyudi (STKIP PGRI Jombang, 2019)
The novel Sepertiga Malam di Manhattan by Arumi E is very interesting to study. This novel is a novel about the struggle of a family to get happiness. This novel is the Arumi E's 27th newest novel. The struggle in this novel is to make the family happy, expecting for the baby. Before writing the novel, Arumi E did a research in the places written in the novel to achieve a very interesting fictional story and most of this story was taken from the traveling results so it was so interesting. The objective of this research is to describe (1) the Autopoetic System in the novel Sepertiga MalamdiManhattan by Arumi E. (2) The differentiation system in the Novel Sepertiga Malamdi Manhattan by Arumi E.The research method used is in the form of a descriptive qualitative method that uses a social system approach. The method used by the researcher is the dialectical method. The data source used in this research is the novel Sepertiga Malamdi Manhattan by Arumi E, published by Gramedia publisher in 2018. The data collection in this study uses the steps of reading the novel. To collect data, the researcher use any instrument.There are two results of the study: (1) The autopoetic system in the novel Sepertiga MalamdiManhattan by Arumi E. is concerning to some characters who have their own beliefs or rules in their lives who do not want to follow the rules of others, they are more confident in their own way to success and purpose of life. (2) The system of differentiation in the novel Sepertiga Malamdi Manhattan by Arumi E. is covering the handling of changes in the environment, the characters are able to adapt to the new environment, which has a different culture from the original culture. This shows evidence of the system autopoetic and differentiation in the novel Sepertiga MalamdiManhattan by Arumi E.